Modelling urban scenes for LBMS - António Fernando Coelho (2005)
Three-dimensional graphical applications can provide an added value to Location Based Mobile Services (LBMS). This is particularly true for the applications related to urban environments, which can interactively present three-dimensional models to the user, visualized in accordance to his location. Modelling an urban environment is mainly a manual procedure and so it can become a difficult, tedious and time consuming task, due to the many different geometries, textures, details, etc, involved in the urban structures. This paper presents the XL3D modelling system that provides, in an automatic fashion, three-dimensional models of urban areas to be used in a LBMS Project. The XL3D modelling system is based on interoperable access to digital data, in diverse formats, accessing XML documents or invoking Web services in a distributed architecture. The system is driven by L-systems based modelling processes that automatically generate three-dimensional models of urban environments, specified in a declarative mode using documents based on an XML Schema, also called XL3D. Copyright © 2005 by the Association for Computing Machinery, Inc.